Cosmetic reconstruction in breast cancer patients: Opportunities for nanocomposite materials. (1st March 2019) - Prasad, Karthika; Zhou, Renwu; Zhou, Rusen; Schuessler, David; Ostrikov, Kostya Ken; Bazaka, Kateryna
Graphical abstract: Abstract: The most common malignancy in women, breast cancer remains a major medical challenge that affects the life of thousands of patients every year. With recognized benefits to body image and self-esteem, the use of synthetic mammary implants for elective cosmetic augmentation and post-mastectomy reconstruction continues to increase. Higher breast implant use leads to an increased occurrence of implant-related complications associated with implant leakage and rupture, capsular contracture, necrosis and infections, which include delayed healing, pain, poor aesthetic outcomes and the need for revision surgeries. Along with the health status of the implant recipient and the skill of the surgeon, the properties of the implant determine the likelihood of implant-related complications and, in doing so, specific patient outcomes. This paper will review the challenges associated with the use of silicone, saline and "gummy bear" implants in view of their application in patients recovering from breast cancer-related mastectomy, and investigate the opportunities presented by advanced functional nanomaterials in meeting these challenges and potentially opening new dimensions for breast reconstruction. Statement of Significance: Breast cancer is a significant cause of morbidity and mortality in women worldwide, which is difficult to prevent or predict, and its treatment carries long-term physiological and psychological consequences. Post-mastectomy breast reconstruction addresses the cosmetic aspect of cancer treatment. Yet, drawbacks of current implants contribute to the development of implant-associated complications, which may lead to prolonged patient care, pain and loss of function. Nanomaterials can help resolve the intrinsic biomechanical mismatch between implant and tissues, enhance mechanical properties of soft implantable materials, and provide an alternative avenue for controlled drug delivery. Here, we explore advances in the use of functionalized nanomaterials to enhance the properties of breast implants, with representative examples that highlight the utility of nanomaterials in addressing key challenges associated with breast reconstruction.